Pengaruh Sektor Perikanan Terhadap PDB Indonesia - Desta Sari, Catur; Khoirudin, Rifki (Perwira Journal of Economics & Business, 2023)
The fisheries sector is one of the economic activities that has a big role for people's lives. About 2/3 of Indonesia's territory is the ocean. Therefore, the potential of fish in Indonesia is very abundant, fisheries are also included in one of the renewable natural resource sectors. With the fisheries sector, the potential for biodiversity has great opportunities to be developed, such as food sources, sources of industrial raw materials and cosmetics, and support for industrial development and tourism. This study aims to find out how influential the fisheries sector is on those represented by GDP. The data used is secondary data derived from the official website of the World Bank, the Central Statistics Agency, the Ministry of Fisheries and Fisheries of Indonesia, and Bank Indonesia using the regression model assumption test. Based on the results and language in the study, the variable number of Fishery Production has a positive and significant effect on GDP, Inflation has a negative and significant effect on GDP, and the Dollar Exchange Rate has a positive and significant effect on GDP. Meanwhile, the Labor variable has an insignificant effect on GDP.